Coating slurry and aluminum foil double-side coated carbon material prepared from coating slurry
By using coating slurry with graphite powders and tackifiers of different particle size ranges in thermal interface materials, the problems of insufficient thermal conductivity and poor mechanical properties in the prior art are solved, and efficient thermal conductivity and good performance are achieved. mechanical properties.
Patent Information
- Application Number
- CN202411595850.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
AI Technical Summary
The thermal conductivity between components during the semiconductor etching process of existing thermal interface materials is insufficient, and the mechanical properties and deformation resistance are poor, so they cannot effectively resist gas corrosion and impact.
It provides a coating slurry containing graphite powder, vinyl silicone oil, hydrogen-containing silicone oil and tackifier of different particle size ranges. Through suitable particle size ratios and additive ratios, the thermal conductivity and electrical conductivity of the slurry are improved. The adhesion between the slurry and the substrate is enhanced by a tackifier.
It improves the interface force, cohesion and tensile-breaking ability of aluminum foil double-sided carbon coated material, combines good thermal conductivity, and extends the life of the material.
Smart Images

Figure BDA0005126879370000101 
Figure HDA0005126879380000011 
Figure HDA0005126879380000012
Abstract
Description
Technical Field
[0001] The invention belongs to the field of thermal interface materials, and in particular relates to a thermally conductive and electrically conductive material required to be filled between components during semiconductor etching and a preparation method thereof. Background Art
[0002] When the surfaces of two non-completely mirrored materials come into contact, some air will fill the gaps at the interface, and the air has high thermal resistance and electrical resistance, resulting in decreased thermal / electrical conductivity between the materials. Thermal interface materials are mainly used between heating devices and heat dissipation devices to reduce the contact thermal resistance between the two materials. In the etching process of semiconductor chip production, the contact thermal resistance and contact resistance problems between various mechanical components are more significant, especially when corrosive gases are introduced, and the requirements for material stability are getting higher and higher. At the same time, the material is also required to have a certain degree of deformation resistance to resist gas corrosion and impact.
[0003] Current thermal interface materials are mostly made of polymer resin materials mixed with aluminum oxide / aluminum nitride or other metal compounds. Some products will add a small amount of conductive carbon black to reduce resistance. They can be mainly divided into thermal conductive gel, thermal conductive silicone grease, thermal conductive gaskets, phase change materials, etc.
[0004] Thermally conductive gel / silicone grease materials use silicone resin binders and inorganic powders as fillers. Although they have high thermal conductivity and fit well with components, they basically have no mechanical properties and the cleaning process is cumbersome. They are not suitable for large-area coating and are used in specific thermal conductive fields such as CPUs and gratings. The thermal conductivity of thermal conductive gasket materials can reach up to 12W, and their volume resistivity is >10^12Ω·m. They have good insulation properties, but poor mechanical properties, weak resistance to deformation and shear force, and thicker gasket bond thickness (BLT), generally 0.25~5mm. They are mostly used in related fields such as thermal conductivity and non-conductivity, and cannot be used in scenarios that require conductive properties.
[0005] It is urgent to discover a new type of thermal and electrical conductive material to solve the problems existing in the existing technology. Summary of the invention
[0006] The present invention aims at the problems existing in the prior art and provides a coating slurry, wherein the coating slurry comprises a reaction product of vinyl silicone oil, hydrogen-containing silicone oil, inorganic powder, a tackifier, an auxiliary agent and a diluent;
[0007] 20-30 parts by weight of the vinyl silicone oil, 2-10 parts by weight of hydrogenated silicone oil, 27-48 parts by weight of inorganic powder, 2-10 parts by weight of tackifier, 0.55-1.10 parts by weight of auxiliary agent, and 30-50 parts by weight of diluent;
[0008] Furthermore, the viscosity of the vinyl silicone oil is in the range of 500 to 5000 mPa·s;
[0009] Furthermore, the hydrogen content of the hydrogen-containing silicone oil is 0.04 to 0.20 wt %;
[0010] Further, the inorganic powder includes three graphites of different particle sizes, the D50 particle size range of the first graphite is 1 to 3 μm, the D50 particle size range of the second graphite is 4 to 7 μm, and the D50 particle size range of the third graphite is 8 to 15 μm;
[0011] Furthermore, the first graphite is 15 to 25 parts by mass, the second graphite is 8 to 14 parts by mass, and the third graphite is 4 to 9 parts by mass;
[0012] Further, the tackifier includes one or more combinations of aminopolysiloxane, epoxy resin modified polysiloxane, methacrylic acid modified polysiloxane, and vinyl polysiloxane;
[0013] Preferably, the tackifier is epoxy resin modified polysiloxane;
[0014] Further, the viscosity of the coating slurry ranges from 2000 to 5000 mPa·s;
[0015] Furthermore, the vinyl silicone oil is 24 parts by mass, with a viscosity of 2500mPa·s, the hydrogen-containing silicone oil is 3 parts by mass, with a hydrogen content of 0.08wt%, the first graphite is 18 parts by mass, with a D50 particle size range of 1 to 3μm, the second graphite is 10 parts by mass, with a D50 particle size range of 4 to 7μm, the third graphite is 5 parts by mass, with a D50 particle size range of 8 to 15μm, the tackifier is 7 parts by mass of epoxy resin modified polysiloxane, the auxiliary agent is 0.78 parts by mass, the diluent is 35 parts by mass, and the viscosity of the coating slurry is 3400mPa·s.
[0016] The second aspect of the present invention provides a method for preparing a coating slurry A1, wherein vinyl silicone oil, a catalyst, an inhibitor, a dispersant, and a diluent are sequentially added into a double planetary stirring kettle equipped with a high-speed dispersion disk, and the kettle body is cooled with circulating water at a temperature of 20 to 25°C, a rotation speed of 110 n / min, a dispersion disk of 50 to 60 Hz, and stirring is performed for 30 minutes, and then hydrogen-containing silicone oil and a tackifier are added, the dispersion disk is 50 to 60 Hz, the rotation speed is 110 n / min, and stirring is performed for 30 minutes, and finally, inorganic powder is added, the dispersion disk is 50 to 60 Hz, 100 n / min, and stirring is performed for 120 minutes;
[0017] The third aspect of the present invention provides an aluminum foil double-sided carbon-coated material, which is prepared by the following method: using a slit extrusion device, the aluminum foil has a thickness of 0.04 to 0.10 mm and a width of 300 to 600 mm;
[0018] S1, A surface coating: transfer the prepared coating slurry A1 into the feeding tank, control the extrusion volume by the screw pump speed, 200-4000mL / min, wet film coating thickness 0.2-0.5mm, vehicle speed 1-10m / min, oven temperature 80-170℃, and roll up the coating slurry A1 after drying in the oven;
[0019] S2, coating of side B: place the dried coil on side A at the discharge end, repeat the previous step, and then roll it up and store it after drying in an oven;
[0020] S3, finally slice and shape the product according to its size.
[0021] Beneficial effects:
[0022] (1) The present invention proposes a coating slurry, which contains graphite powder with different particle size ranges. The thermal and electrical conductivity of the slurry can be improved by selecting a suitable graphite powder particle size ratio and addition ratio. In addition, the viscosity enhancer also enhances the adhesion between the slurry and the substrate.
[0023] (2) The present invention proposes an aluminum foil double-sided carbon-coated material. The above-mentioned coating slurry contains vinyl silicone oil and hydrogen-containing silicone oil, so that the aluminum foil double-sided carbon-coated material prepared by the slurry has strong interfacial force and cohesive force, and good tensile strength. Selecting aluminum foil as the substrate can achieve good mechanical properties. The aluminum foil double-sided carbon-coated material coated with the slurry also has good thermal and electrical conductivity, and takes into account the characteristics of long service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 The surface of the double-sided carbon-coated aluminum foil material in Example 1 of the present invention;
[0026] Figure 2 This is the cross section of the double-sided carbon-coated aluminum foil material in Example 1 of the present invention. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] <Coating slurry>
[0029] The first aspect of the present invention provides a coating slurry, the coating slurry comprising a reaction product of vinyl silicone oil, hydrogen-containing silicone oil, inorganic powder, a tackifier, an auxiliary agent and a diluent;
[0030] Vinyl silicone oil
[0031] Vinyl silicone oil includes one or more combinations of terminal vinyl silicone oil, side vinyl silicone oil, and terminal-side vinyl silicone oil; terminal vinyl silicone oil refers to silicone oil with vinyl end-capping at at least one end, and the crosslinking density of single-terminal vinyl silicone oil is lower than that of double-terminal vinyl silicone oil; side vinyl silicone oil is silicone oil with vinyl end-capping on the side chain of the molecular chain, which can increase the crosslinking density; terminal-side vinyl silicone oil is silicone oil with vinyl groups at both ends and sides of the molecular chain, and has a higher degree of crosslinking.
[0032] The double-terminated vinyl silicone oil in the present invention has a better effect because its cross-linking degree is moderate and the cross-linking density can be controlled to obtain ideal overall mechanical properties.
[0033] In the present invention, the viscosity of the vinyl silicone oil is in the range of 500 to 5000 mPa·s.
[0034] When the viscosity of vinyl silicone oil is too low, its molecular chain is shorter and the interaction between the chains is weak, which will make the material brittle. At the same time, low-viscosity vinyl silicone oil has better fluidity, but the network structure it forms may not be tight enough. Such a network lacks sufficient support and has weaker bonding force, making it more likely to break. When the viscosity of vinyl silicone oil is too high, the fluidity becomes worse, resulting in longer molding time, difficult molding, and reduced molding efficiency.
[0035] Hydrogen silicone oil
[0036] Hydrogenated silicone oil includes one or more combinations of single-end or double-end hydrogenated silicone oil, side hydrogenated silicone oil, and end-side hydrogenated silicone oil. Single-end or double-end hydrogenated silicone oil refers to hydrogenated silicone oil with Si-H located on one or both sides of the molecular chain, which can be used as a chain extender. Double-end hydrogenated silicone oil, due to its bifunctional structure, does not cause crosslinking, but extends the molecular chain of vinyl silicone oil, which can reduce the crosslinking density; side hydrogenated silicone oil refers to hydrogenated silicone oil with Si-H located on the side of the molecular chain, which can be used as a crosslinking agent to improve the mechanical properties of the material; end-side hydrogenated silicone oil refers to hydrogenated silicone oil with Si-H located on both ends and sides of the molecular chain, and its degree of crosslinking is higher than the other two types of hydrogenated silicone oils;
[0037] In the present invention, the side hydrogenated silicone oil is preferred, which can provide better mechanical properties after addition reaction. Because the side hydrogenated silicone oil can react with multiple vinyl silicone oil molecules during the crosslinking process to form a more complex crosslinked network structure, rather than a simple point crosslinking, such a crosslinked network can effectively increase the crosslinking density of the material and enhance the mechanical properties of the material.
[0038] The hydrogen content of the hydrogen-containing silicone oil in the present invention is 0.04-0.20wt%.
[0039] When the hydrogen content is too low, the number of hydrogen atoms that can participate in the cross-linking reaction is reduced, resulting in insufficient cross-linking. This means that the network structure formed by the material after curing is not tight enough, lacks good mechanical properties, and leads to poor toughness of the material; while excessive hydrogen content will cause more hydrogen atoms to participate in the reaction, which will significantly increase the activity and rate of the reaction. Too fast a reaction rate may make it difficult to accurately control the reaction conditions. In reactions with high hydrogen content, more heat is usually released, causing the local temperature to rise, further accelerating the reaction rate, which makes it more difficult to control the reaction. In addition, when the hydrogen content is too high, the viscosity of the material may change drastically during the reaction, thereby affecting the fluidity and processing performance, and increasing the complexity of the reaction process.
[0040] Inorganic powder
[0041] In the present invention, the inorganic powder includes three graphites with different particle size ranges, the D50 particle size range of the first graphite is 1-3 μm, the D50 particle size range of the second graphite is 4-7 μm, and the D50 particle size range of the third graphite is 8-15 μm.
[0042] Graphite powders of different particle sizes can form a more compact stacking structure. Small particles (such as the first graphite) can fill the gaps between larger particles (such as the second and third graphite), thereby improving the density of the overall material without causing molding problems. In addition, this dense structure helps to reduce the conduction path of heat and electrons and improve thermal and electrical conductivity. Particles with smaller particle sizes provide more contact surfaces and form a better thermal and electrical network, allowing heat and electrons to be conducted more efficiently within the material, while larger particles help to enhance the overall thermal and electrical conductivity of the material.
[0043] Tackifier
[0044] In the present invention, the tackifier includes one or more combinations of aminopolysiloxane, epoxy resin modified polysiloxane, methacrylic acid modified polysiloxane, and vinyl siloxane, preferably epoxy resin modified polysiloxane.
[0045] Additives
[0046] In the present invention, the auxiliary agents include catalysts, inhibitors and dispersants.
[0047] In the present invention, the catalyst includes one or a combination of a Castel Pt catalyst and a chloroplatinic acid catalyst, preferably a Castel Pt catalyst; in the present invention, the inhibitor includes one or more combinations of maleates, fumarates, alkynes, and organic phosphines, preferably maleates, and more preferably diallyl maleate; in the present invention, the dispersant includes one or more combinations of polyvinyl pyrrolidone, carboxymethyl cellulose, and sodium lignin sulfonate, preferably polyvinyl pyrrolidone.
[0048] Thinner
[0049] In the present invention, the diluent includes one or more combinations of n-hexane, n-heptane, and n-butanol, preferably n-heptane.
[0050] Ratio of each material
[0051] In the present invention, 20 to 30 parts by weight of vinyl silicone oil, 2 to 10 parts by weight of hydrogenated silicone oil, 27 to 48 parts by weight of inorganic powder, 2 to 10 parts by weight of tackifier, 0.55 to 1.10 parts by weight of auxiliary agent, including 0.5 to 1.0 parts by weight of catalyst, 0.02 to 0.04 parts by weight of inhibitor, 0.03 to 0.06 parts by weight of dispersant, and 30 to 50 parts by weight of diluent.
[0052] In the present invention, the amount of vinyl silicone oil and hydrogen silicone oil affects the crosslinking degree and viscosity of the slurry, and affects the interface force, cohesive force and tensile strength of the double-sided carbon-coated aluminum foil material prepared by using the slurry in the next step; the particle size ratio and addition ratio of the graphite powder affect the thermal and electrical conductivity of the slurry, and the thermal and electrical conductivity of the slurry can be improved by selecting a suitable particle size ratio and addition ratio of the graphite powder; the amount of the thickener not only affects the viscosity of the slurry, but also affects the adhesion between the slurry and the substrate in the next step; the auxiliary agent includes a catalyst, an inhibitor and a dispersant, the amount of the catalyst affects the reaction rate, the amount of the inhibitor affects the speed of the curing reaction, the amount of the dispersant affects the dispersion performance of the coating slurry, and also affects the uniformity and adhesion of the coating material; the amount of the diluent can regulate the viscosity of the slurry.
[0053] In the present invention, the first graphite is 15 to 25 parts by mass, the second graphite is 8 to 14 parts by mass, and the third graphite is 4 to 9 parts by mass.
[0054] Fine particles (such as the first graphite) can fill the gaps between larger particles (such as the second and third graphite), and the appropriate mass ratio can ensure the formation of effective heat and electron conduction paths between inorganic powders of different particle sizes. A high proportion of fine particles or medium particles may cause internal particle aggregation, which cannot effectively fill the gaps between the third graphite particles, resulting in insufficient filling. This unevenness will cause the interruption of the heat and electron conduction paths, resulting in discontinuity of the thermal and electrical conduction paths, and reduce the thermal and electrical conduction performance; while too many coarse particles may form dead corners for heat and electron conduction, affecting the flow of heat and electrons.
[0055] Viscosity
[0056] In the present invention, the viscosity of the coating slurry is in the range of 2000 to 5000 mPa·s. The viscosity has a significant impact on the coating effect, and a suitable viscosity is beneficial to the subsequent preparation of the coating material.
[0057] High viscosity slurries have poor fluidity during the coating process, which may lead to uneven coating and inconsistent coating thickness. During the coating process, high viscosity slurries may clog the nozzles, affecting the efficiency of the operation. High viscosity may also lead to poor wettability between the slurry and the substrate, affecting the adhesion of the coating. High viscosity slurries usually contain more solid components, causing the coating to release water or solvents more slowly when drying, thereby prolonging the drying time.
[0058] Low viscosity slurries flow easily, which may result in insufficient coating thickness and failure to achieve the expected performance requirements. Too low a viscosity may result in the slurry not being able to fully adhere to the substrate, reducing the adhesion and durability of the coating. Although low viscosity slurries release water or solvents quickly when drying, if they dry too quickly, they may cause problems such as cracks or peeling on the surface of the coated material.
[0059] In the present invention, the coating slurry is further preferably a reaction product comprising the following raw materials: 24 parts by mass of vinyl silicone oil with a viscosity of 2500mPa·s, 3 parts by mass of hydrogenated silicone oil with a hydrogen content of 0.08wt%, 18 parts by mass of first graphite with a D50 particle size range of 1 to 3μm, 10 parts by mass of second graphite with a D50 particle size range of 4 to 7μm, 5 parts by mass of third graphite with a D50 particle size range of 8 to 15μm, 7 parts by mass of epoxy resin modified polysiloxane as a tackifier, 0.78 parts by mass of an auxiliary agent, 35 parts by mass of a diluent, and the viscosity of the coating slurry is 3400mPa·s.
[0060] <Preparation of coating slurry>
[0061] The second aspect of the present invention provides a method for preparing a coating slurry A1: vinyl silicone oil, catalyst, inhibitor, dispersant, and diluent are added in sequence to a double planetary stirred kettle equipped with a high-speed dispersion disk, the kettle body is cooled with circulating water, the temperature is 20-25°C, the rotation speed is 110n / min, the dispersion disk is 50-60Hz, and stirring is carried out for 30min, then hydrogen-containing silicone oil and thickener are added, the dispersion disk is 50-60Hz, the rotation speed is 110n / min, and stirring is carried out for 30min, and finally inorganic powder is added, the dispersion disk is 50-60Hz, 100n / min, and stirring is carried out for 120min.
[0062] <Aluminum foil double-sided carbon coated material>
[0063] The third aspect of the present invention provides an aluminum foil double-sided carbon-coated material, which is prepared by the following method: using a slit extrusion device, the aluminum foil thickness is 0.04-0.10 mm, the width is 300-600 mm, and the model is 8011-H18 / H14 / H22;
[0064] S1, A surface coating: transfer the prepared coating slurry A1 into the feeding tank, control the extrusion volume by the screw pump speed, 200-4000mL / min, wet film coating thickness 0.2-0.5mm, vehicle speed 1-10m / min, oven temperature 80-170℃, and roll up the coating slurry A1 after drying in the oven;
[0065] S2, coating of side B: place the dried coil on side A at the discharge end, repeat the previous step, and then roll it up and store it after drying in an oven;
[0066] S3, finally slice and shape the product according to its size.
[0067] The above and other advantages of the present invention may be better understood through the following examples, but the following examples are not intended to limit the scope of the present invention.
[0068] Example
[0069] The present invention is described below with reference to the following examples, but the present invention is not limited to the following examples.
[0070] Example 1
[0071] This embodiment provides a coating slurry A1, comprising the following components in parts by weight:
[0072] 24 parts of vinyl silicone oil (viscosity 2500mPa·s, vinyl content 0.30%), 3 parts of hydrogen-containing silicone oil (viscosity 230mPa·s, hydrogen content 0.08wt%), first graphite (D50 particle size range of 1 to 3μm, carbon content 99.9%, density 0.76g / cm 3, graphitization degree 94.20%) 18 parts, the second graphite (D50 particle size range is 4-7μm, carbon content is 99.98%, density is 0.43g / cm 3 , graphitization degree 94.47%) 10 parts, the third graphite (D50 particle size range is 8-15μm, carbon content is 99.98%, density is 1.06g / cm 3 , graphitization degree 94.20%) 5 parts, tackifier is epoxy resin modified polysiloxane 7 parts, catalyst is Custer Pt catalyst (platinum content 5000ppm) 0.7 parts, inhibitor is diallyl maleate 0.03 parts, dispersant is polyvinyl pyrrolidone 0.05 parts, diluent is n-heptane 35 parts, to prepare coating slurry A1.
[0073] This embodiment also provides a method for preparing the coating slurry A1:
[0074] Vinyl silicone oil, catalyst, inhibitor, dispersant, and diluent were added to a double planetary stirring kettle equipped with a high-speed dispersion disk. The kettle was cooled with circulating water at a temperature of 23°C, a speed of 110n / min, and a dispersion disk of 50Hz. Stirring was performed for 30min. Then hydrogenated silicone oil and thickener were added. The dispersion disk was 50Hz, the speed was 110n / min, and stirring was performed for 30min. Finally, inorganic powder was added. The dispersion disk was 50Hz, 100n / min, and stirring was performed for 120min. The viscosity of the coating slurry A1 was measured to be 3400mPa·s.
[0075] This embodiment also provides an aluminum foil double-sided carbon-coated material, which is prepared using the following method, including the following steps:
[0076] Using slot extrusion equipment, aluminum foil thickness 0.06mm, model 8011-H22, width 600mm;
[0077] S1, A surface coating: transfer the prepared coating slurry A1 to the feeding tank, control the extrusion volume by the screw pump speed, 600mL / min, wet film coating thickness 0.35mm, vehicle speed 3m / min, oven temperature 90-150℃. The coating slurry A1 is rolled up after drying in the oven;
[0078] S2, B side coating: Place the dried coil on the A side at the discharge end, repeat the previous step, and then roll it up and store it after drying in an oven.
[0079] S3, slice and shape according to product size.
[0080] Example 2
[0081] The difference from Example 1 is that the vinyl silicone oil is 20 parts, the hydrogenated silicone oil is 2 parts, the first graphite is 15 parts, the second graphite is 8 parts, the third graphite is 4 parts, the tackifier is 2 parts, the catalyst is 0.5 parts, the inhibitor is 0.02 parts, the dispersant is 0.03 parts, and the diluent is 30 parts. The other reagents and preparation methods are the same as those in Example 1. The viscosity of the coating slurry obtained using this formula is 3650 mPa·s.
[0082] Example 3
[0083] The difference from Example 1 is that the vinyl silicone oil is 30 parts, the hydrogenated silicone oil is 10 parts, the first graphite is 25 parts, the second graphite is 14 parts, the third graphite is 9 parts, the tackifier is 10 parts, the catalyst is 1.0 parts, the inhibitor is 0.04 parts, the dispersant is 0.06 parts, and the diluent is 50 parts. The other reagents and preparation methods are the same as those in Example 1. The viscosity of the coating slurry obtained using this formula is 3020 mPa·s.
[0084] Example 4
[0085] The difference from Example 1 is that the viscosity of the vinyl silicone oil is 400 mPa·s, and the hydrogen content of the hydrogen-containing silicone oil is 0.30 wt %. Other reagents and preparation methods are the same as those in Example 1. The viscosity of the coating slurry obtained using this formula is 1800 mPa·s.
[0086] Example 5
[0087] The difference from Example 1 is that the viscosity of the vinyl silicone oil is 5500 mPa·s, and the hydrogen content of the hydrogen-containing silicone oil is 0.03 wt %. Other reagents and preparation methods are the same as those in Example 1. The viscosity of the coating slurry obtained using this formula is 5200 mPa·s.
[0088] Example 6
[0089] The difference from Example 1 is that the D50 particle size of the first graphite is in the range of 1 to 2 μm, the D50 particle size of the second graphite is in the range of 4 to 5 μm, and the D50 particle size of the third graphite is in the range of 8 to 10 μm. Other reagents and preparation methods are the same as those in Example 1. The viscosity of the coating slurry obtained using this formula is 3650 mPa·s.
[0090] Example 7
[0091] The difference from Example 1 is that the D50 particle size of the first graphite is in the range of 2 to 3 μm, the D50 particle size of the second graphite is in the range of 5 to 7 μm, and the D50 particle size of the third graphite is in the range of 10 to 15 μm. Other reagents and preparation methods are the same as those in Example 1. The viscosity of the coating slurry obtained using this formula is 3300 mPa·s.
[0092] Example 8
[0093] The difference from Example 1 is that the D50 particle size of the first graphite is in the range of 0.5 to 1 μm, the D50 particle size of the second graphite is in the range of 7 to 9 μm, and the D50 particle size of the third graphite is in the range of 15 to 18 μm. Other reagents and preparation methods are the same as those in Example 1. The viscosity of the coating slurry obtained using this formula is 3300 mPa·s.
[0094] Comparative Example 1
[0095] The difference from Example 1 is that the vinyl silicone oil is 10 parts, the hydrogenated silicone oil is 1 part, the first graphite is 10 parts, the second graphite is 5 parts, the third graphite is 3 parts, the tackifier is 0.5 parts, the catalyst is 0.1 parts, the inhibitor is 0.01 parts, the dispersant is 0.02 parts, and the diluent is 20 parts. The other reagents and preparation methods are the same as those in Example 1. The viscosity of the coating slurry is measured to be 7200 mPa·s.
[0096] Comparative Example 2
[0097] The difference from Example 1 is that the vinyl silicone oil is 40 parts, the hydrogenated silicone oil is 11 parts, the first graphite is 40 parts, the second graphite is 15 parts, the third graphite is 10 parts, the tackifier is 15 parts, the catalyst is 1.2 parts, the inhibitor is 0.05 parts, the dispersant is 0.07 parts, and the diluent is 70 parts. The other reagents and preparation methods are the same as those in Example 1. The viscosity of the coating slurry is measured to be 1560 mPa·s.
[0098] The above embodiments and comparative examples were subjected to the following performance tests:
[0099] Thermal conductivity test: Take five groups of samples at different positions for thermal conductivity test, and finally take the average value. Test equipment: Xiangtan Xiangyi DRL-III (heat flow method), test method ASTM 5470-06.
[0100] Conductivity test: Take five groups of samples at different positions for conductivity test and take the average value. Test equipment: ST2258C multifunctional digital four-probe tester, test method ASTMF390-11.
[0101] Adhesion test: Take five groups of samples at different positions for conductivity test and take the average value. Shimadzu universal tensile testing machine AGS-X, test method GB5210-85.
[0102] Mechanical properties test: Take five groups of samples at different positions for conductivity test and take the average value. Shimadzu universal tensile testing machine AGS-X, test method GB / T 1040.1-2018.
[0103] Application evaluation test: Machine model: GASKET;
[0104] Test data: inner top temp 103℃; Outer temp top temp 113.6℃ / 115.6℃ / 115.9℃;
[0105] Particles: 25ea; Lifespan: 500h.
[0106] The test results are shown in Table 1:
[0107] Table 1
[0108]
[0109] It should be noted that, according to the explanation and elaboration of the above description, those skilled in the art to which the present invention belongs may also make changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments disclosed and described above, and some equivalent modifications and changes to the present invention should also be within the scope of protection of the claims of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the invention.
Claims
1. A coating slurry, characterized in that: The coating slurry comprises a reaction product of vinyl silicone oil, hydrogen-containing silicone oil, inorganic powder, tackifier, auxiliary agent and diluent; The vinyl silicone oil is 20 to 30 parts by weight, the hydrogenated silicone oil is 2 to 10 parts by weight, the inorganic powder is 27 to 48 parts by weight, the tackifier is 2 to 10 parts by weight, the auxiliary agent is 0.55 to 1.10 parts by weight, and the diluent is 30 to 50 parts by weight.
2. The coating slurry according to claim 1, characterized in that: The viscosity of the vinyl silicone oil is in the range of 500 to 5000 mPa·s.
3. The coating slurry according to claim 1, characterized in that: The hydrogen content of the hydrogen-containing silicone oil is 0.04-0.20wt%.
4. The coating slurry according to claim 1, characterized in that: The inorganic powder includes three graphites with different particle size ranges, the D50 particle size range of the first graphite is 1-3 μm, the D50 particle size range of the second graphite is 4-7 μm, and the D50 particle size range of the third graphite is 8-15 μm.
5. The coating slurry according to claim 1, characterized in that: The first graphite is 15 to 25 parts by mass, the second graphite is 8 to 14 parts by mass, and the third graphite is 4 to 9 parts by mass.
6. The coating slurry according to claim 1, characterized in that: The tackifier includes one or more combinations of amino polysiloxane, epoxy resin modified polysiloxane, methacrylic acid modified polysiloxane, and vinyl polysiloxane, and is preferably epoxy resin modified polysiloxane.
7. The coating slurry according to claim 1, characterized in that: The viscosity of the coating slurry is in the range of 2000 to 5000 mPa·s.
8. The coating slurry according to any one of claims 1 to 7, characterized in that: The vinyl silicone oil comprises 24 parts by mass and has a viscosity of 2500mPa·s, the hydrogen-containing silicone oil comprises 3 parts by mass and has a hydrogen content of 0.08wt%, the first graphite comprises 18 parts by mass and has a D50 particle size range of 1 to 3μm, the second graphite comprises 10 parts by mass and has a D50 particle size range of 4 to 7μm, the third graphite comprises 5 parts by mass and has a D50 particle size range of 8 to 15μm, the tackifier comprises 7 parts by mass of epoxy resin modified polysiloxane, the auxiliary agent comprises 0.78 parts by mass, the diluent comprises 35 parts by mass, and the viscosity of the coating slurry is 3400mPa·s.
9. A method for preparing a coating slurry, characterized in that: Into a double planetary stirring kettle equipped with a high-speed dispersing disk, vinyl silicone oil, catalyst, inhibitor, dispersant and diluent are added in sequence, and circulating water is added to cool the kettle body. The temperature is 20-25°C, the speed is 110n / min, the dispersing disk is 50-60Hz, and stirring is carried out for 30min. Then, hydrogenated silicone oil and tackifier are added. The dispersing disk is 50-60Hz, the speed is 110n / min, and stirring is carried out for 30min. Finally, inorganic powder is added. The dispersing disk is 50-60Hz, 100n / min, and stirring is carried out for 120min.
10. A double-sided carbon-coated aluminum foil material, characterized in that: The following method was used for preparation: using a slot extrusion device, the thickness of the aluminum foil was 0.04-0.10 mm and the width was 300-600 mm; S1, coating of surface A: transfer the prepared coating slurry as claimed in any one of claims 1 to 8 into a feeding tank, control the extrusion volume by the screw pump speed, 200 to 4000 mL / min, wet film coating thickness 0.2 to 0.5 mm, vehicle speed 1 to 10 m / min, oven temperature 80 to 170°C, and roll up the coating slurry as claimed in any one of claims 1 to 8 after drying in the oven; S2, coating of side B: place the dried coil on side A at the discharge end, repeat the previous step, and then roll it up and store it after drying in an oven; S3, finally slice and shape according to product size.
Citation Information
Patent Citations
Heat conducting composite material and heat conducting composite sheet prepared by applying same
CN103146198A
Heat-conducting silica gel as well as preparation method and application thereof
CN111004510A
Packaging material and preparation method and application thereof
CN117777732A
Curable resin composition and metal-based circuit substrate by using the same
JP2005281509A
Polyorganosiloxane and thermally conductive silicone composition thereof
US20220220259A1